2014
DOI: 10.1016/j.ijpsycho.2013.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Using music as a signal for biofeedback

Abstract: Studies on the potential benefits of conveying biofeedback stimulus using a musical signal have appeared in recent years with the intent of harnessing the strong effects that music listening may have on subjects. While results are encouraging, the fundamental question has yet to be addressed, of how combined music and biofeedback compares to the already established use of either of these elements separately. This experiment, involving young adults (N = 24), compared the effectiveness at modulating participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 30 publications
0
36
0
1
Order By: Relevance
“…Second, given the known potential for significant improvement with training in mu-based BCI devices (Neuper et al, 2006), novices such as those tested here have the potential with continued training to significantly improve accuracy and facility with the instrument. The use of scalar musical tones—rather than non-musical sound or visual biofeedback—may confer a training advantage: the benefits of music for arousal motivation for both training and therapeutics have been shown (Bergstrom et al, 2014). Third, the use of a musical feedback-based EEG device with responsiveness noticeable to the user may hold promise for patients—such as those with locked-in syndrome—who are severely incapacitated and may be more likely to respond to auditory (and specifically musical) stimulus and feedback than to visual stimulus and feedback.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, given the known potential for significant improvement with training in mu-based BCI devices (Neuper et al, 2006), novices such as those tested here have the potential with continued training to significantly improve accuracy and facility with the instrument. The use of scalar musical tones—rather than non-musical sound or visual biofeedback—may confer a training advantage: the benefits of music for arousal motivation for both training and therapeutics have been shown (Bergstrom et al, 2014). Third, the use of a musical feedback-based EEG device with responsiveness noticeable to the user may hold promise for patients—such as those with locked-in syndrome—who are severely incapacitated and may be more likely to respond to auditory (and specifically musical) stimulus and feedback than to visual stimulus and feedback.…”
Section: Discussionmentioning
confidence: 99%
“…However, Bergstrom et al (2014) showed musical biofeedback to be better than either simple passive music listening or non-musical sonification biofeedback for control of physiological arousal state. Here we report reasonable control with virtually no training, using scalar musical tone feedback rather than non-musical auditory feedback.…”
Section: Discussionmentioning
confidence: 99%
“…There is ample research evidence showing that listening to music can have an effect on activity in the limbic system, considered to be the brain's emotional core (Blood and Zatorre, 2001; Koelsch, 2010; Peretz et al, 2013), and might lead to that “spreading gooseflesh, hair-on-end feeling” better known as “chills” (Panksepp, 1995). Used as a biofeedback system, it has been shown that music may modulate physiological arousal (Bergstrom et al, 2014). It is important to acknowledge that emotional responses to music and sound are tied to individuals' personal traits, preferences familiarity, and music-related autobiographic memories (Kreutz et al, 2007; Barrett et al, 2010).…”
Section: Motivation By Musical Biofeedbackmentioning
confidence: 99%
“…Thereby, auditory biofeedback systems commonly map physiological and physical quantities to psychoacoustic (sound) parameters, such as loudness, pitch, timbre, and rhythm (Hermann and Hunt, 2005; Dubus and Bresin, 2013). Studies that explicitly use music as auditory biofeedback however are relatively scarce (Bergstrom et al, 2014; Moens et al, 2014; Van Dyck et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“… 4 Utilizing music‐induced analgesia is not new to migraine. Music has been included in biofeedback training 5 and commonly accompanies web‐based or downloaded applications that our more computer savvy patients utilize.…”
mentioning
confidence: 99%